2019
DOI: 10.4018/978-1-5225-7056-1.ch011
|View full text |Cite
|
Sign up to set email alerts
|

Women's Leadership Aspirations and Career Paths in Higher Education

Abstract: The purpose of this chapter is to provide insight into the ways in which personal life roles such as mother, daughter, and/or spouse/partner influence the leadership aspirations of women holding senior university administrative positions (e.g., academic dean, vice president, provost). The chapter is informed by a postmodern feminist perspective and reviews literature related to pathways to the presidency, family considerations, gender roles, and geographic mobility. Findings from the literature are integrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Similarly, another respondent in the study shared that several of his colleagues, who had held administrative positions, expressed how much they disliked the leadership role and actively dissuaded him from ever pursuing such a position. As Hill (2003) noted, there is a prevalence of this feeling of unpreparedness and reluctance, particularly in the experiences of department heads she studied. Gunsalus (2006) stated that it is a major transition from professor, "where one largely controls one's own intellectual agenda," to an administrative position where the demands of others and priorities of the department or faculty become your focus (p. 12).…”
Section: Context At the Individual Levelmentioning
confidence: 93%
See 2 more Smart Citations
“…Similarly, another respondent in the study shared that several of his colleagues, who had held administrative positions, expressed how much they disliked the leadership role and actively dissuaded him from ever pursuing such a position. As Hill (2003) noted, there is a prevalence of this feeling of unpreparedness and reluctance, particularly in the experiences of department heads she studied. Gunsalus (2006) stated that it is a major transition from professor, "where one largely controls one's own intellectual agenda," to an administrative position where the demands of others and priorities of the department or faculty become your focus (p. 12).…”
Section: Context At the Individual Levelmentioning
confidence: 93%
“…Adding to this challenge is that many academic leaders, particularly the middle-management roles like department heads, accept the job reluctantly and are often ambivalent about assuming the role. The role itself is often characterized by a lack of understanding from faculty on what the role entails (Hill, 2003;Kezer & Lester, 2011). M' Gonigle and Starke (2006) recognized the opposition from faculty to corporate models but nonetheless suggested that learning from such models may ironically be the best way to address the need for system innovation.…”
Section: Leadership Development In Higher Educationmentioning
confidence: 99%
See 1 more Smart Citation